EXPERIMENTAL SIMULATION OF POST-OPERATIVE COGNITIVE DISORDERS IN RATS - I. V. Belozertseva; O. A. Dravolina; V. O. Krivov; M. A. Tur; Yu. S. Polushin (Вестник анестезиологии и реаниматологии)
Goal: to develop the design of the experiment for evaluation of cognitive functions and behavior of rats after some aggressive impact imitating anesthesia and surgery in the clinical practice. Methods: Male rats of Wistar stock (n = 40) were used to evaluate long-term behavioral effects of the abdomen surgery and short-term (15-20 min.) and long-term (6 hours) actions of halothane. Simple (2x2) factorial plan was used for the experiment (4 blocks, balanced as per the number of animals from 4 experimental groups, n=2 for each group in the block). For anesthesia induction 4 volumes of % halothane in the air flow (2 l/min) were used, for anesthetic support it was 1.5 volume of % halothane. During surgery the rat was placed on the heated operating table and the mask was used for anesthesia. Laparotomy was performed; empty intestine was identified and irritated for 10 seconds by massage movement of the forefinger and thumb. After that the loop was placed into the abdomen and the wound was sutured layer by layer. Then for three weeks the following behavioral tests were performed in compliance with the protocol: motor activity (Actometer) and exploratory activity in new environment (Open field), social behavior (pair interaction test), novel object recognition, extrapolational deliverance rate, forced swimming, sexual behavior. Ovariectomized female (n = 16) were used as standard opponents for social behavior tests, and hormone-stimulated female rats (n = 26) were used for sexual behavior tests. The results showed that long-term action of halothane vapor caused behavioral changes in rats: it reduces exploratory activity, decreases the novel object recognition index, increases immobility during forced swimming and reduces latent period of extrapolational deliverance. Halothane made no significant impact on motor activity (open field) and sexual behavior of male rats. In general the results of performed tests provide evidence of emotional flattening development in rats. Conclusion: It is feasible to use the experiment design and pool of behavioral tests used in this study for experimental evaluation of inhalation anesthetics effects, their late consequences, and also for searching the ways of management of the developing behavioral disorders.